INDIVIDUAL DIFFERENCES IN BRAIN ACTIVITIES WHEN HUMAN WISHES TO LISTEN TO MUSIC CONTINUOUSLY USING NEAR-INFRARED SPECTROSCOPY - Shin-ichi Ito, Momoyo Ito, Minoru Fukumi (International Journal of Advanced Science and Technology, 2020)
This paper introduces an individual difference in the activities of the prefrontal cortex when a person wants to listen to music using near-infrared spectroscopy. The individual differences are confirmed by visualizing the variation in oxygenated hemoglobin level. The sensing positions used to record the brain activities are around the prefrontal cortex. The existence of individual differences was verified by experiments. The experiment results show that active positions while feeling a wish to listen to music are different in each subject, and an oxygenated hemoglobin level is different in each subject compared to its value when a subject does not feel the wish to listen to music. The experiment results show that it is possible to detect a wish to listen to the music based on changes in the oxygenated hemoglobin level. Also, these results suggest that active positions are different in each subject because the sensitivities and how to feel on stimulus are different. Lastly, the results suggest that it is possible to express the individual differences as differences in active positions.